Application of Wood Composites - Réh, Roman; Krišťák, Ľuboš (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue "Application of Wood Composites" addresses various aspects of these important wood materials' use. Topics include the mechanical processing of wood composites, including their cutting, milling, or sanding, incorporating current analysis of wood dust or grain size measurements and the composition of particles; scientific views on the influence of various adhesives in the creation process of wood composites and the analysis of their behavior in contact with various wood elements under different conditions; the analysis of input raw materials forming wood composites, including various wood species, but also non-wood lignocellulosic raw materials; and, last but not least, the analysis of bark, which in recent years has become an important and promising raw material involved in the construction of wood composites. The study of the development of the sliding table saw also suitably complements this Special Issue.